IMPLEMENTASI KETERLIBATAN ORANG TUA DALAM MODEL EPSTEIN DI CENDEKIA KIDS SCHOOL MADIUN - Annisa Putri Noerviana; Rosyida Nurul Anwar; Dian Ratnaningtyas Afifah (Program Studi PG PAUD Universitas PGRI Ronggolawe, 2024)
Parental involvement in early childhood education is a process or way for families, especially parents, to participate and play a role in organizing education to achieve goals. According to experts, there are several models for parental involvement, one of which is the Epstein model. Epstein frames six forms of parental involvement: parenting education, communication, volunteering, learning at home, decision-making, and community collaboration. The benefits of parental involvement in early childhood education are that parents gain knowledge regarding child development, the relationship between parents and teachers is well established, and the school's image is good. Parental involvement indeed cannot be separated from supporting and inhibiting factors. This research aims to determine parent involvement in the Epstein model at Pakar Kids School. The subjects of this research were the principal, teachers, and parents at Pakar Kids School. This research method uses a qualitative approach with a field research type. Research location at Pakar Kids School. Data collection techniques through interviews and documentation. The data analysis technique for this research uses the Miles and Huberman model, namely data reduction, data presentation, and concluding. The research results show that the Epstein model of parent involvement is relevant to parent involvement at Pakar Kids School, which takes six forms: parenting education, communication, volunteering, learning at home, decision-making, and collaborating with the community. Supporting factors for parental involvement are school readiness and the relationship or communication that exists between parents and teachers. Meanwhile, the factors inhibiting parental involvement are parental education and employment.